Integrated Dual-Output L-Z Source Inverter for Hybrid Electric Vehicle - Deepankar E.; Chauhan A.K.; Singh S.K. (My University, 2025)
A single-stage converter simultaneously supplying the power to dc and ac load is an interesting solution. Cost saving, better efficiency, and independent control of both outputs (in a restricted range) are the key features achieved in a single-stage converter. Switched boost, boost, and L-Z source inverter (LZSI)-derived hybrid converters are the potential solutions reported in the literature. These converters have a restricted range of controlling the output voltage independently. To widen the range of independent control, this paper presents a three-winding mutually coupled inductor-based LZSI. Initially, this topology is developed as a DC-DC converter, which is further extended for hybrid output applications. Though the duty cycle is varied in the range of 0 < D < 1, the gain achieved using this topology is higher than its counterparts. The gain of the proposed inverter is derived analytically and validated experimentally. To investigate the characteristics of the inverter, the open-loop transfer function is derived, which is further utilized to design the closed-loop control. The theoretical design of closed loop is validated experimentally. © 2015 IEEE.